A Crystallographic Study of a Series of Nitrobenzoic Acid Co-crystals and Molecular salts - Scheepers, Matthew (My University, 2018)
Co-crystals are structures in which two or more neutral components are present in the same crystal structure. This differs in comparison to salts, where ionically charged species exist within the structure. Co-crystals and salts are deployed frequently within the pharmaceutical industries as a means to improve the physical properties of active pharmaceutical ingredient(s) (API) with unsuitable physical properties. Nitrobenzoic acids are present in many important pharmaceutical ingredients, and have been reported in the literature to frequently form many co-crystals and salts. This study focuses on four particular nitrobenzoic acids: 2-chloro-4-nitrobenzoic acid, 2-chloro-5-nitrobenzoic acids, 3,5-dinitrobenzoic acid and 4-nitrobenzoic acid with the goal of determining the suitability of these compounds in co-crystal/salt formation. These compounds did form co-crystals/salts by using suitable co-formers, which did include several drugs such as flufenamic acid and theophylline (drugs which have been reported in the literature has having poor physical properties). These co-crystals and molecular salts had their structures determined using single crystal X-ray diffraction (SC-XRD), and thermal properties such as melting points determined using differential scanning calorimetry (DSC). The melting points of the co-crystals/salts reported here are indeed different to the respective co-formers, which indicates that new physical properties have arisen in comparison to the respective co-formers.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. 2018, Johannesburg